If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7 = 4a + 7 Reorder the terms: 7 + 6x = 4a + 7 Reorder the terms: 7 + 6x = 7 + 4a Add '-7' to each side of the equation. 7 + -7 + 6x = 7 + -7 + 4a Combine like terms: 7 + -7 = 0 0 + 6x = 7 + -7 + 4a 6x = 7 + -7 + 4a Combine like terms: 7 + -7 = 0 6x = 0 + 4a 6x = 4a Solving 6x = 4a Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '6'. x = 0.6666666667a Simplifying x = 0.6666666667a
| (x+(x+8)+(10+(x+8)))=125 | | 100-3x=33x+24 | | 3x^2-3x+2=2x^2+x-1 | | 25r^2-25r+6=0 | | 20z+-3z+-13z=-20 | | -0.00512y+1.7787=12.007y-1.005 | | -0.00512y+1.7132=13.002y-1.008 | | -0.0512y+1.7132=13.002y-1.008 | | -0.00378y+1.6781=13.002y-1.008 | | (80-x)10=10 | | 89x+56=67 | | 17=5x+5y | | 50-90x=89 | | Cos(8x)+cos(4x)+2cos(2x)=0 | | 45-89x=-78 | | 2v+2u+5u= | | 79x-76=90 | | x^2+20x+4800=0 | | 78x+76=89 | | x+84=-82 | | x-3=2(x-4) | | 34x-68=79 | | -18=3(3x-3) | | 5(5x+1)=-20 | | P^4-14p^2+40=0 | | -4x+28=-x+7 | | 57x-98=978 | | 45x+78=980 | | 45x+78=98 | | 2c^4-6c^3-12c^2+36c=0 | | 67x+34=173 | | 67x+34=67 |